2020
DOI: 10.15672/hujms.617303
|View full text |Cite
|
Sign up to set email alerts
|

Proportional hazards model under ranked set sampling scheme using censored data of coronary heart disease

Abstract: The proportional hazards model is one of the most common model for analyzing survival data. Only proportional hazards assumption is required to apply this model. Using appropriate sampling methods is an important part of modelling data and estimation of parameters. In literature there is a few studies based on sampling methods in survival analysis and most of them are related with non-parametric estimations of survival functions, sample size calculation etc. The main innovation of our approach is to examine th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 35 publications
(41 reference statements)
0
1
0
Order By: Relevance
“…In such situations, it is shown that ranked set sampling (RSS), provided by McIntyre, 1 is a better alternative and more informative than SRS. Thus, RSS has been widely applied in many disciplines including medicine, 2 information theory, 3 quality control 4 and fuzzy analysis. 5…”
Section: Introductionmentioning
confidence: 99%
“…In such situations, it is shown that ranked set sampling (RSS), provided by McIntyre, 1 is a better alternative and more informative than SRS. Thus, RSS has been widely applied in many disciplines including medicine, 2 information theory, 3 quality control 4 and fuzzy analysis. 5…”
Section: Introductionmentioning
confidence: 99%